Barriers to the implementation of cloud computing for sustainable construction in a developing economy - Oke, A.E. (Emerald Group Holdings Ltd., 2021)
Purpose: The purpose of this paper is to investigate the applicability of cloud computing (CC) and the challenges that contribute to more successful projects with a major sustainable construction development. Design/methodology/approach: The previous studies provided information on CC implementation barriers, which were then evaluated by 104 construction stakeholders through a questionnaire survey. As a result, the exploratory factor analysis (EFA) approach was used to investigate these barriers. Furthermore, a partial least square structural equation model was used to build a model of these barriers (PLS-SEM). Findings: The EFA results revealed that the above-noted factors are in a close relation with three key components, i.e. social, economic and communication. In addition, the proposed model results found the social barrier a key challenge to the implementation of CC. Research limitations/implications: The results from this study can help decision-makers to improve the approaches regarding data fragmentation that has great effects on the execution of all construction projects. The focus of the paper is to enhance the data fragmentation processes. In addition, the results would be useful to strengthen the sustainability of existing construction projects by enhancing the implementation of CC. Originality/value: The novelty of this research work will provide a solid foundation for critically assessing and appreciating the different barriers affecting the adoption of CC. Â© 2021, Emerald Publishing Limited.